2017
DOI: 10.1097/prs.0000000000003602
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment Algorithm for Patients Presenting with Sagittal Craniosynostosis after the Age of 1 Year

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…Other centers have shown that patients with SS who present at older than 1 year often present without significant scaphocephaly, frontal bossing, or occipital protuberance. 37 Patients presenting to our center at younger ages presented with more severe scaphocephaly and increased relative posterior vault volume suggesting occipital protuberance; children presenting at older ages presented with more severe middle vault constriction. 3 When assessing for predictors of long-term morphometric outcomes in SS, we found that preoperative severity was the best predictor across all measurements.…”
Section: Discussionmentioning
confidence: 94%
“…Other centers have shown that patients with SS who present at older than 1 year often present without significant scaphocephaly, frontal bossing, or occipital protuberance. 37 Patients presenting to our center at younger ages presented with more severe scaphocephaly and increased relative posterior vault volume suggesting occipital protuberance; children presenting at older ages presented with more severe middle vault constriction. 3 When assessing for predictors of long-term morphometric outcomes in SS, we found that preoperative severity was the best predictor across all measurements.…”
Section: Discussionmentioning
confidence: 94%
“…[14][15][16][17][18][19] Thus, this group of patients falls into the subset of "normocephalic" sagittal craniosynostosis as described by Morritt et al and Ruane and colleagues. 4,12 Although an incidental suture fusion in this age group is abnormal, it is unclear whether it has any clinical importance. None of the 11 computed tomographic scans that demonstrated a fused suture showed radiographic findings suggestive of elevated intracranial pressure, and volume analysis on this subset of patients was normal with the exception of the one patient with Rett syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…La prĂ©dominance masculine est retrouvĂ©e aussi bien dans la littĂ©rature [6] Actuellement, l'examen de rĂ©fĂ©rence pour la craniostĂ©nose est le scanner cĂ©rĂ©bral (fait dans 15,38% dans notre sĂ©rie), mais dans les pays en cours de dĂ©veloppement par faute de moyens et d'accessibilitĂ©, la radiographie standard reste largement utilisĂ©e (76,92% dans notre Ă©tude) et demandĂ©e dans 66% des cas dans l'Ă©tude de ECH-CHAFAIY [10]. En ce qui concerne l'IRM, dans la littĂ©rature, la prĂ©valence sur l'existence d'une anomalie parenchymateuse reste faible Ă  l'IRM [11] ; ces anomalies sont Ă  type de ventriculomĂ©galie essentiellement pour une atteinte de la suture sagittale et au niveau de la rĂ©gion mĂ©diane une diminution du volume du corps calleux surtout sur son segment postĂ©rieur, et une diminution du volume du cervelet.…”
Section: Discussionunclassified
“…La suspension n'est pas nĂ©cessaire pour la chirurgie des craniostĂ©noses. La technique chirurgicale varie selon le type de la craniostĂ©nose [6]. La rĂ©alisation d'un remodelage complet doit ĂŞtre rĂ©servĂ©e pour les enfants plus de 4 mois ; avant 4 mois, il faut faire une simple craniotomie bipariĂ©tale [19].…”
Section: Discussionunclassified